2013
DOI: 10.1007/s11064-013-1066-4
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Treatment Transiently Increases the Permeability of Brain Capillary Endothelial Cells Through Translocation of Claudin-5

Abstract: The blood-brain-barrier (BBB) is formed by different cell types, of which brain microvascular endothelial cells are major structural constituents. The goal of this study was to examine the effects of cooling on the permeability of the BBB with reference to tight junction formation of brain microendothelial cells. The sensorimotor cortex above the dura mater in adult male Wistar rats was focally cooled to a temperature of 5 °C for 1 h, then immunostaining for immunoglobulin G (IgG) was performed to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…44, 63, 64 The claudin-5 staining similar to that of ZO-1 suggesting that claudin-5 is also localized to the junction in the VWF −/− mice. The role of basement membrane proteins in tight junction protein expression is so far under-explored.…”
Section: Discussionmentioning
confidence: 75%
“…44, 63, 64 The claudin-5 staining similar to that of ZO-1 suggesting that claudin-5 is also localized to the junction in the VWF −/− mice. The role of basement membrane proteins in tight junction protein expression is so far under-explored.…”
Section: Discussionmentioning
confidence: 75%
“…Our studies focused only on the effects of TGFβ1 on claudin-5 expression and demonstrated that treatment of bEnd.3 cells with rTGFβ1 downregulated claudin-5 and led to the translocation of this protein from the cell membrane to the cytosol. Claudin-5 downregulation has been shown to lead to increased BBB permeability following hypoxia(35), focal cerebral cooling(36), and ischemia reperfusion injury(37). Also, other studies have found that TGFβ1 can lead to the direct downregulation of claudin-5(38).…”
Section: Discussionmentioning
confidence: 99%
“…ZO-1 and claudin-5 are the most important components for cell barrier integrity. Claudin-5 can greatly reduce dextran permeability and improve transendothelial electrical resistance [31], and plays an essential role in the earliest stage of CNS angiogenesis [32]. ZO-1 serves as a bridge between transmembrane proteins and skeleton proteins, and this interaction is important to the stability and function of endothelial barrier [33], [34].…”
Section: Discussionmentioning
confidence: 99%